Bentuk preparasi akhiran servikal mahkota porcelain fused to metal mempengaruhi insidensi gingivitis pada gigi insisivus sentralis rahang atas Preparation shape of cervical edge of porcelain fused to metal crown affect incidence of gingivitis at maxillary central incisive teeth - Abd. Karim; Moh. Dharmautama; Edy Machmud (DiscoverSys Inc., 2013)
The selection of cervical edge form of porcelain fused to metal (PFM)crown is very important because it is associatedwith the incidence of gingivitis. Improper types of cervical edge may cause a gap at the edge; which is a good place forthe growth and development of dental plaque bacteria that play a major role in the occurrence of inflammation. Thisstudy aims to determine the effect of the cervical edge preparation shape of PFM crown against bacterial plaqueadhesion and tissue inflammation supporting abutments, as well as to determine the best shape of the cervical edgepreparation for PFM crown restoration. This Clinical experimental research with time series design is performed to 3groups of cervical edge preparation design, i.e. shoulder, bevel shoulder and deep chamfer. Sample of 15 peopledivided equally into the 3 groups. Examination of the clinical signs of gingivitis (gingival discoloration, bleeding onprobing, and pocket depth) and the number of bacterial colonies were performed before tooth preparation; 1, 7, and 21days after insertion. The data were processed statistically by ANOVA. The results showed the form shoulder bevel edgegives the most noticeable impact to gingivitis than other types.